Adaptation through occupation multidimensional perspectives - Boisselle, Angela K.; Grajo, Lenin C. (SLACK Incorporated, 2019)
Adaptation, as an internal human process, is an often-overlooked construct in occupational therapy education, research, and practice. Adaptation Through Occupation: Multidimensional Perspectives aims to change that by presenting different perspectives that challenge the reader's understanding of occupational adaptation. As the first of its kind text to explore, analyze, and present a comprehensive and multidimensional approach to understanding occupational adaptation, the collection of writings in this text add to the range of knowledge available in occupational therapy. Adaptation Through Occupation: Multidimensional Perspectives by Drs. Lenin Grajo and Angela Boisselle provides in-depth perspectives of occupation and adaptation that can be used to teach courses on foundational and theoretical perspectives in occupational therapy, occupational science undergraduate and graduate programs, and as a critical module in teaching Neuroscience to occupational therapy students. This text also aims to facilitate new bodies of research to define and apply the concept of adaptation in relation to occupational performance and participation. Some perspectives covered inside include: - Historical and theoretical perspectives on occupation and adaptation - Neural mechanisms of occupational adaptation - Occupational science perspectives and international and lived-experience perspectives Instructors in educational settings can visit www.efacultylounge.com for additional materials to be used in the classroom. Adaptation Through Occupation: Multidimensional Perspectives opens the gates for new ways of understanding occupational adaptation and adds necessary information to the existing knowledge in the occupational therapy profession"--